PENGARUH PEMBERIAN APERSEPSI KEMAMPUAN DASAR MATEMATIKA TERHADAP KEMAMPUAN SISWA MENYELESAIKAN SOAL KESETIMBANGAN BENDA TEGAR - Kaswara, Ihpar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aimed to find out the effect of apperception of basic mathematical ability on students’ to solve question on equilibrium rigid body and to find out differences in student ability to solve question on equilibrium rigid body reviewed by low, medium, and high of basic mathematics ability. The method of research used was pre-experimental research with one–Group Pretest-Posttest Design. The instruments were essay basic mathematics ability, pretest and posttest. The sample are 25 students’ which were using the intac group method. Data collected was analysed using mean score while t test and anava one way was used to the test hypothesis The result shows that there is positive effect of apperception of basic mathematical ability on students’ to solve question on equilibrium rigid body (P-value < 0,05). There are differences in student ability to solve question on equilibrium rigid body among the groups of low, medium, and high of basic mathematics ability (P-value < 0,05). Keywords : Apperception, Apperception on Basic Mathematics ability, Equilibrium rigid body